THE SITUATION IN THE MIDDLE EAST AFTER THE 80-IES OF THE XX CENTURY AND THE BEGINNING OF THE XXI CENTURY (Annual of the Faculty of Philosophy in Skopje, 2016)
At the end of XX century, there were a lot of changes caused, in front of all, by the fall of the Berlin Wall, the perestroika in the USSR and the collapse of the Warsaw Pact. That brought these changes to have an impact on the events in the Middle East. It was accompanied by wars between nations and peoples who inhabited this territory. The situation was fueled by local leaders who wanted to expand the territories at the expense of the other countries. Among these leaders it was Khomeini, who wanted to spread the Islamic revolution from Iran in all Arab countries, as well as Saddam Hussein who wanted Iraq to become the most powerful country in the Arab world. It led to war that took great material damage and a lot of lives. Similar was the situation in Israel where the fights which began in the 50’s of XX century proceeded to the end of the century.
Keywords: STATE OF ISRAEL; PALESTINE; IRAQ; IRAN; KHOMEINI; SADDAM HUSSEIN; YASSER ARAFAT